Off-label use of rituximab in patients with systemic lupus erythematosus with extrarenal disease activity: a retrospective study and literature review - Sans-Pola, Carla; Danés, Immaculada; Bosch, Josep Àngel; Marrero-Álvarez, Patricia; Cortés, Josefina; Agustí, Antònia (Frontiers in Medicine, 2023)
Introduction: Off-label rituximab is commonly used for patients with systemic lupus erythematosus (SLE) with extrarenal disease activity. Methods: The outcomes and tolerability of rituximab in adult patients with non-renal SLE treated at our hospital from 2013 to 2020 were described. Patients were followed-up until December 2021. Data were retrieved from electronic medical records. Response was classified into complete, partial or no response according to the Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI 2K)-based definitions. Results: A total of 44 cycles were administered to 33 patients. Median age was 45 years and 97% were female. Median follow-up was 5.9 years (IQR 3.7-7.2). The most frequent symptoms that motivated rituximab use were thrombocytopenia (30.3%), arthritis (30.3%), neurological manifestations (24.2%) and cutaneous lupus (15.2%). After most treatment cycles a partial remission was achieved. The median SLEDAI-2K score declined from 9 (IQR 5-13) to 1.5 (IQR 0-4) (p<0.00001). The median number of flares significantly declined after receiving rituximab. Platelet counts significantly improved in patients with thrombocytopenia and patients with skin disorders or neurological manifestations also had a partial or complete response. Only 50% of patients with a predominant joint involvement had either a complete or a partial response. The median time to relapse after the first cycle was 1.6 years (95% CI, 0.6-3.1). Anti-dsDNA levels decreased significantly after rituximab from a median of 64.3 (IQR 12-373.9) to 32.7 (IQR 10-173), p=0.00338. The most frequent adverse events were infusion-related reactions (18.2%) and infections (57.6%). All patients needed further treatment to maintain remission or to treat new flares. Conclusions: A partial or complete response was documented after most rituximab cycles in patients with non-renal SLE. Patients with thrombocytopenia, neurolupus, and cutaneous lupus had better response than those with a predominant joint involvement.